Effect of Return on Assets, Corporate Governance and Sales Growth on Tax Avoidance in Companies Food and Beverage Sub Sector Manufacturing Registered in stock Exchange Indonesia - Sumarno Manrejo; An Nisa Mar'atus Sholihah; Markonah Markonah (Management Research Studies Journal, 2023)
This study aims to determine the effect of Return on Assets, Corporate Governance and Sales Growth on Tax Avoidance. The population in this study are all food and beverage sub-sectors manufacturing companies listed on the Indonesia Stock Exchange in 2017-2021. The sampling technique used was purposive sampling with 25 data samples. While the data analysis technique used is multiple linear regression through SPSS 26. The method used is quantitative method using secondary data. the the results showed that the variables Return On Assets, Audit Committee and Sales Growth simultaneously had a positive and significant effect on tax avoidance. Partially Return On Assets has a negative and significant effect on taxes avoidance, audits Committee has a negative and significant effect on taxes avoidance and Sales Growth has a negative and significant effect.